ANALGESIC EFFECT OF DIRECT BREASTFEEDING DURING BCG VACCINATION IN HEALTHY NEONATES - Dar, Jawad Yousaf; Goheer, Lutfullah; Shah, Sajid Ali (Journal of Ayub Medical College Abbottabad, 2019)
Background: Pain during painful procedures in neonates has far reaching consequences. In developed countries many non-pharmacological interventions are used for neonatal pain reduction. Breast feeding has been proved to be an effective analgesic during mild to moderate painful procedures in neonates. Methods: The study, randomized controlled trial was conducted in CMH, Quetta. The study period extended from June to November 2015. Neonates included in the experimental group were breastfeed during BCG vaccination and neonates in the control group were provided with routine care. Duration of cry with needle insertion was recorded with a digital stopwatch till the baby is silent for more than 5 seconds. Results: The mean crying duration in experimental group was significantly less than control group. In experimental group mean crying duration was 16.48s (12.76) whereas in control group mean crying duration was 34.93 s(45.26). Statistically significant difference was observed between the mean crying times of the two groups (p<0.05). Conclusion: Mean duration of crying with breastfeeding is shorter than without breast feeding during BCG immunization. Breast feeding reduces pain during minor painful procedures in neonates. Keywords: breast feeding; neonatal pain; BCG; Immunization